Electrophysical properties of composites based on the epoxy resin and expanded graphite - O. G. Sirenko; S. M. Makhno; O. M. Lisova; G. M. Gunya; P. P. Gorbyk (Хімія, фізика та технологія поверхні)
The composites of epoxy resin-expanded graphite(EG)-vermiculite and epoxy resin-expanded graphite-perlite were obtained and their electrophysical properties were analysed at low frequencies and in the microwave range.